Leveraging poor people’s access to ownership and benefits of community-based forest enterprises: the role of an adaptive collaborative management approach - Pandit, B.H.; McDougall, C.; Belcher, B.; Kumar, C.; Maharjan, M.R. (2008)
This paper examines the influence of an adaptive collaborative management approach (ACM) on poor people’s control over, and benefits from, a community-based non-timber forest product (NTFP) network enterprise in the Eastern Hills of Nepal. The approach involved shifts in governance and management, especially regarding inclusion of marginalized people and the development of risk and uncertainty analysis. The major outcome of the network’s adoption of this approach is a redistribution of control over livelihood benefits from NTFP resources towards the “poorest of the poor” families in the enterprise area. Another notable change is that network members shifted from working in relative isolation to building alliances and greater interdependence, a change that helped mitigate conflicts between them regarding benefit sharing. Significant enterprise ownership and decision-making opportunities have been created for these poorer households by providing them access to revolving funds that enable them to become shareholders in the network enterprise. Furthermore, because of the learning-based collective action, this network has been able to increase its profit margin from sale of processed NTFPs.